2008
DOI: 10.1086/588459
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Mass‐Dependent Star Formation History of Late‐Type Galaxies Using X‐Ray Emission: Results from the Chandra Deep Fields

Abstract: Wolf, C. (2008) 'Tracing the mass-dependent star formation history of late-type galaxies using X-ray emission : results from the Chandra Deep Fields.', Astrophysical journal., 681 (2). pp. 1163-1182. Further information on publisher's website: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full biblio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 167 publications
(247 reference statements)
15
109
1
Order By: Relevance
“…Similar behavior is also noted in an earlier analysis of the stacked X-ray properties of early-type galaxies in a 1.4 deg 2 field in the NOAO Deep Wide-Field Survey (Brand et al 2005). (Note, however, in a study of late-type galaxies, Lehmer et al (2008) find no evidence for evolution of the AGN fraction over the redshift range 0.1 < z < 0.8.) In the left panel of Figure 13, we show curves for PLE (∝ (1 + z) 3 ; gray dotted line) and for LDDE, another popular model for the evolution of the AGN XLF (∝ (1 + z) 4 ; gray dashed line).…”
Section: Comparison To Previous Field Fractionssupporting
confidence: 83%
“…Similar behavior is also noted in an earlier analysis of the stacked X-ray properties of early-type galaxies in a 1.4 deg 2 field in the NOAO Deep Wide-Field Survey (Brand et al 2005). (Note, however, in a study of late-type galaxies, Lehmer et al (2008) find no evidence for evolution of the AGN fraction over the redshift range 0.1 < z < 0.8.) In the left panel of Figure 13, we show curves for PLE (∝ (1 + z) 3 ; gray dotted line) and for LDDE, another popular model for the evolution of the AGN XLF (∝ (1 + z) 4 ; gray dashed line).…”
Section: Comparison To Previous Field Fractionssupporting
confidence: 83%
“…Webb et al (2009) showed that all of the 8 μm detected LABs have rest-frame near-IR colors consistent with an AGN or ULIRG spectral energy distributions (SED). To examine the possibility that LAB 1, LAB 5, and LAB 16 host heavily obscured AGN (or low-luminosity AGN below the detection limit) we stack the X-ray map at these three positions using the technique outlined in Lehmer et al (2008). We find a marginally significant (93.6% confidence) excess of 6.6 counts compared to 3.5 expected from the background.…”
Section: Searching For X-ray Undetected Agn In Labsmentioning
confidence: 92%
“…A detailed description of the expected spectra of the different components may be found in Persic & Rephaeli (2002). The relative importance of the spectral components may vary; however, in most cases the average flux ratio between the 0.5-2.0 keV and the 2.0-10 keV bands is the same that would be obtained if the spectrum was a power-law spectrum with spectral index Γ = 2.1 and negligible absorption (RCS03; Lehmer et al 2008). This does not imply the lack of X-ray absorption of X-rays in SF galaxies: M 82 and NGC 3256 are notable examples (RCS03; Ranalli et al 2008).…”
Section: X-ray Characterization Of the Selected Sourcesmentioning
confidence: 99%